Politizar la violencia: migración, violencia sexo-genérica y cuidados comunitarios - Stang, María Fernanda (2022)
This article deals with gender-sex violence as a significant expression of the structural nature of gender and sexuality in migratory processes. From the biographical approach, expressions of the multiple forms that this violence acquires (direct, structural, cultural) are addressed in the narratives of ten cis and trans migrant women of Latin American origin who reside in the cities of Antofagasta and Santiago, located in the north and central Chile, respectively, and who have an active participation in social organizations that carry out community care tasks, although these labours are not part of the purposes and main actions of these organizations. The approach is carried out around the idea of politicization in two senses: first, from the proposal to politicize sex-gender violence that is, to make visible the power relations that make it possible and the historical processes that have led to the construction of “violent” bodies and lives from the framework that intersects gender and sexuality with foreignness, ethnicity, “race” and class, among other dimensions; and, second, from the analysis of experiences of politicization of some of these migrant women in which this sex-gender violence is re-signified as the engine of their social participation, a re-signification crossed by the tensions and contradictions that this channeling of participatory action in tasks characterized by sex-gender inequality such as care implies. Although it is concluded that the scope of these experiences in the transformation of this sex-gender violence is fundamentally limited to the individual scale of intradomestic violence, it is proposed that these organizational experiences, in their daily actions and practices, silently and in the long run term undermine the liminality of the foreigner in relation to the recognition of rights by the State of residence, which harbors transformative potentialities of the idea of citizenship, at least from that practical dimension.